The triple bottom line: Green accounting's ripple effect on financial statements - Huda Alsayed (New Applied Studies in Management, Economics & Accounting)
Sustainability encompasses social, economic, and environmental factors to calculate the organization's performance. This study aimed to integrate sustainability into an organization's financial reporting by using the Triple Bottom line framework, which includes social, environmental, and economic aspects. This study took place in the Kingdom of Saudi Arabia in 2023 using the financial report for 2022. Furthermore, thematic and documentary analyses were incorporated to conduct the research. Interviews were conducted with ten management participants. Organizations must evaluate the factors affecting the financial statements and their reporting. Many studies highlight environmental factors such as the economic environment, the political environment, the development of the stock market, and the privatization of state-owned corporations. To further assess the social, economic, and environmental factors, a detailed document has been incorporated and analyzed to understand the ripple effect of green accounting on financial statements. An interview was also conducted with ten participants from the management of an anonymous company, and the themes from their responses were analyzed the ripple effect and role of the TBL The result shows a framework to integrate the concept of sustainability with the financial statements. The study highlighted that green accounting influences the organization's financial health, reputation, and strategic positioning. The subject of this study has great potential and needs to be explored further.